2009
DOI: 10.1038/tpj.2009.37
|View full text |Cite|
|
Sign up to set email alerts
|

Association of polymorphisms in the carbonic anhydrase 6 gene with salivary buffer capacity, dental plaque pH, and caries index in children aged 7–9 years

Abstract: Carbonic anhydrase VI is a secreted enzyme that catalyzes the hydration of carbon hydroxide in saliva and other body fluids. This enzyme has been implicated in taste and gastrointestinal dysfunctions, tooth erosion, and caries. The purpose of this study was to analyze the allele and genotype distribution of three polymorphisms in the coding sequences of (CA6) gene and check for possible associations with salivary buffer capacity, number of decayed, missing, and filled teeth in deciduous and permanent teeth (dm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
49
1
5

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(58 citation statements)
references
References 35 publications
3
49
1
5
Order By: Relevance
“…In 2009, Yarat et al (2009) reported that these studies found no differences in the frequency of the SNPs [rs2274327 (C/T), rs2274328 (A/C)], salivary pH, and buffering capacity among Turkish dental students with caries and those who were caries-free. However, a later study including 245 children investigated the same 2 SNPs and reported that 1 SNP [rs2274327 (C/T)] was associated with a decrease in salivary buffering capacity in healthy children, but that the gene polymorphisms were not directly related to caries (Peres et al, 2010). Recently, 4 SNPs [rs2274327(C/T), rs2274328 (A/C), rs2274329 (G/C), and rs2274330 (G/C)] were studied in 43 subjects, and no correlation was found between SNPs in CA VI exon 2 and salivary buffering capacity or pH; however, a positive significant correlation was found between salivary CA activity and the frequency of SNPs in exon 2 of CA VI in diabetic groups (Koç et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In 2009, Yarat et al (2009) reported that these studies found no differences in the frequency of the SNPs [rs2274327 (C/T), rs2274328 (A/C)], salivary pH, and buffering capacity among Turkish dental students with caries and those who were caries-free. However, a later study including 245 children investigated the same 2 SNPs and reported that 1 SNP [rs2274327 (C/T)] was associated with a decrease in salivary buffering capacity in healthy children, but that the gene polymorphisms were not directly related to caries (Peres et al, 2010). Recently, 4 SNPs [rs2274327(C/T), rs2274328 (A/C), rs2274329 (G/C), and rs2274330 (G/C)] were studied in 43 subjects, and no correlation was found between SNPs in CA VI exon 2 and salivary buffering capacity or pH; however, a positive significant correlation was found between salivary CA activity and the frequency of SNPs in exon 2 of CA VI in diabetic groups (Koç et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, CA VI binds to the enamel pellicle and retains its enzymatic activity on the tooth surface, which may catalyze the conversion of salivary bicarbonate and microbe-delivered hydrogen ions to carbon dioxide and water (Leinonen et al, 1999;Kimoto et al, 2006). It was recently reported that a C/T polymorphism in CA VI may be associated with salivary buffer capacity (Peres et al, 2010). These data suggested that salivary CA VI plays an important role in protecting the teeth from caries.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the study did not account for certain variables which have been demonstrated to effect levels of CA6. For example, polymorphisms of CA6 have been associated with both alterations in taste function and the amount of CA6 produced (Peres et al, 2010;Aidar et al, 2013). Also, when salivary flow rate slows, such as in the case of acute hyperglycemia, CA6 levels decrease (Negrato and Tarzia, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…CA VI enzimi minenin hidroksiapatit kristallerine adsorbe olabilir, pelikıl ve dental biyofilm içerisinde varlığını sürdürebilir. 14,47 Sonuç olarak, tükürük CA VI enzimi oral fizyoloji için anahtar enzim olup, bu enzim ile ilgili çalışmalar devam etmektedir.…”
Section: Karboni̇k Anhi̇draz Enzi̇mi̇unclassified